Accelerating Digital Government through Public Sector Innovation in South Africa: The Role of Open Government Data - Delwa, Qinisile (University of the Witwatersrand, Johannesburg, 2024)
The study aimed to explore the impact of Open Government Data (OGD) on achieving a digital government in South Africa. The study investigated OGD as a public sector innovation and how it contributes to an enhanced approach to designing service- delivery-oriented digital solutions. Experiences of other countries using OGD and its social and economic potential were explored, identifying and comparatively contrasting how such opportunities can be further exploited within the unique circumstances of South Africa. Furthermore, the study reflected on the conception of public sector innovation in practice by observing how this finds expression in existing open government data initiatives to identify potential diffusion mechanisms and opportunities. The motivation for this study is to demonstrate public sector innovation in practice, using OGD as an example of the potential value of public sector innovation that still needs to be explored. The study approach was a qualitative comparative case study where semi-structured interviews were conducted with public sector experts involved in open data projects and independent and retired experts. The data from the interviews was analysed thematically in an inductive approach. The key findings of this research report indicate that South Africa has not made significant progress in digital transformation due to fragmentation and a disjointed strategic approach. The research confirmed the vital role of data, specifically open government data, in advancing digital transformation. Furthermore, based on the case studies, the research findings indicate that open government data-driven public sector innovations hold great potential to accelerate digital government transformation in South Africa
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Innovation Studies to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Digital Government; Public Sector Innovation; South Africa; Open Government Data; UCTD; SDG-9: Industry, innovation and infrastructure